Application of the Mind Mapping Learning Method in Fiqh Subjects at MTS Yapiim Dukuh Indramayu - Dita Lya (COMPETITIVE: Journal of Education, 2022)
The purpose of this study was to find out how the application of the Mind Mapping learning method could increase students' interest in learning Fiqh class VIII A at MTs YAPIIM Dukuh Indramayu. The type of this research is the Mixed Method method, which is a combination of qualitative and quantitative methods. Mixed method is a method that uses a combination of research procedures, where one method is more dominant than the other. Less dominant methods are only positioned as complementary methods as additional data. The complementary method in this research is the qualitative method and the complementary method is the quantitative method. The conclusion of this study is the implementation of the application of the method Mind Mapping learning on Fiqh subjects has a positive influence in increasing student learning interest. There is an increase in student learning interest in fiqh subjects using the Mind Mapping learning method. The results of observations in the first cycle of enthusiasm and activity of class VIII A MTs YAPIIM Dukuh Indramayu were in the good category, namely 66.6% and the observation results of the second cycle have reached 83.3%. Results of the questionnaire/questionnaire Student interest in cycle I was 72.8% and there was an increase in interest in learning in cycle II, namely 76.8% which was in the very high category.